2018
DOI: 10.1097/pcc.0000000000001451
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine as Single Continuous Sedative During Noninvasive Ventilation: Typical Usage, Hemodynamic Effects, and Withdrawal*

Abstract: Dexmedetomidine use for noninvasive positive pressure ventilation sedation in pediatric critical care has predictable hemodynamic effects including bradycardia and hypertension. Although withdrawal was associated with higher cumulative dose, these symptoms were effectively managed with short-term enteral clonidine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 17 publications
0
52
0
2
Order By: Relevance
“…Researchers reported in the literature that doses of 1-4 μg/ kg of dexmedetomidine may cause a temporary increase in blood pressure and reflex bradycardia. Peripheral vasoconstriction due to α2β receptor activation in peripheral arteriol smooth muscles and subsequent sympatholytic effect due to activation of α2C receptors are responsible for suppressing noradrenaline release by "negative feedback"mechanism [19][20][21][22] . Bloor et al reported a 2-minute infusion of dexmedetomidine at a dose of 1 μg/kg and a significant increase in MAP compared to baseline values in the subsequent first minute [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Researchers reported in the literature that doses of 1-4 μg/ kg of dexmedetomidine may cause a temporary increase in blood pressure and reflex bradycardia. Peripheral vasoconstriction due to α2β receptor activation in peripheral arteriol smooth muscles and subsequent sympatholytic effect due to activation of α2C receptors are responsible for suppressing noradrenaline release by "negative feedback"mechanism [19][20][21][22] . Bloor et al reported a 2-minute infusion of dexmedetomidine at a dose of 1 μg/kg and a significant increase in MAP compared to baseline values in the subsequent first minute [23] .…”
Section: Discussionmentioning
confidence: 99%
“…An alternative strategy to prevent DEX withdrawal symptoms involves transitioning DEX to enteral clonidine, another α-2 agonist. [17][18][19][20] Clonidine has been used to prevent and treat withdrawal symptoms associated with several classes of drugs including opioids, alcohol, and nicotine. 15,[21][22][23] It also provides adequate sedation for patients in the PICU and is well tolerated.…”
Section: Introductionmentioning
confidence: 99%
“…Dexmedetomidine is a α2-receptor agonist which provides sedation and analgesia, and it can also reduce heart rate and blood pressure without respiratory depression [3] . Dexmedetomidine can improve postoperative cognitive function and reduce the incidence of early postoperative cognitive dysfunction [4] .…”
Section: Introductionmentioning
confidence: 99%